2004
DOI: 10.1080/15287390490273460
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Dietary Cadmium (Cd) in Rabbit Tissues and Excretions: A Comparison of Lettuce Amended with Soluble Cd Salt and Lettuce with Plant-Incorporated Cd

Abstract: Quantifying the transfer of Cd from foods to mammalian target organs is key to estimating the health risk from this exposure; however, the bioaccumulation of Cd from foods is modified by many dietary components. Studies of dietary Cd absorption would be simpler if it were known that Cd added to foods as a soluble salt was as bioavailable as Cd incorporated during growth of the food species. Rabbits were fed, for 16 d, fresh lettuce containing cadmium incorporated into the lettuce during growth or added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…For both in vivo studies [20,21] as well as the present in vitro studies, lettuce (Latuca sativa L. cv. Ostinata) and durum wheat (Triticum turgidum L. var durum) were grown hydroponically, with and without Cd(NO 3 ) 2 ·H 2 O (500 μg Cd/L) to generate the "incorporated" and "control" diet material.…”
Section: Diet Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For both in vivo studies [20,21] as well as the present in vitro studies, lettuce (Latuca sativa L. cv. Ostinata) and durum wheat (Triticum turgidum L. var durum) were grown hydroponically, with and without Cd(NO 3 ) 2 ·H 2 O (500 μg Cd/L) to generate the "incorporated" and "control" diet material.…”
Section: Diet Materialsmentioning
confidence: 99%
“…In brief, rabbits were fed one of three lettuce diets (control, incorporated or amended) for up to 10 weeks, and this diet was supplemented with Cd free water and alfalfa pellets that contained trace concentrations of Cd. [20] Every 2 weeks, 3 animals from each of the 3 diets were sacrificed; target organs (liver and kidney) as well as the small intestine and samples of blood, urine and feces were collected, and analyzed for Cd concentration. The mice were similarly fed durum grain that had either been amended with, or grown supplied with, Cd·(NO 3 ) 2 ·H 2 O, so that the Cd was differentially associated with the grain.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…In A. halleri leaves, Zn is bound mainly to malate or other organic acids (Sarret et al 2009); Cd is also bound to organic acids, cell wall components and, to a lesser amount, thiol-containing molecules (Huguet et al 2012). Earlier published papers indicated that plant-incorporated metals are often absorbed in greater amounts in comparison to their inorganic forms, which are artificially added to an animal diet (Cadková et al 2013;Chan et al 2004). To our knowledge, this is the first time A. halleri has been used in a feeding study.…”
Section: Resultsmentioning
confidence: 99%
“…In reptiles and other vertebrates, Cd is mainly accumulated in liver, kidney, and pancreas and in the intestinal mucosa (Chan et al 2004;Mann et al 2007;Rie et al 2001;Vogiatzis and Loumbourdis 1998;Weigel et al 1984;Xu and Wang 2002). Intestinal mucosa is rather an organ of transport (Chan et al 2001), and once Cd is absorbed through gastrointestinal tracts into the bloodstream, Cd associates reversibly with plasma proteins (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary transfer, accumulation, kinetics and the effects of Cd have been widely studied in mammals (Chan et al 2004;Lind et al 1997;Matsuno et al 1991;Schilderman et al 1997), whereas little is still known about reptiles (snakes: Hopkins et al 2002;lizards: Mann et al 2007). In those studies, individual animals were contaminated with Cd via food, and distribution in the organs was investigated.…”
Section: Introductionmentioning
confidence: 99%